World Economy and International Business for Students, Researchers and Practitioners - E. V. Zenkina (Vestnik MGIMO-Universiteta)
Book review:  Bulatov A., ed. 2023. World Economy and International Business: Theories, Trends, and Challenges. Springer Cham. 830 p. DOI: 10.1007/978-3-031-20328-2